2004
DOI: 10.1016/j.synthmet.2004.02.014
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the degradation of polyaniline films grown on iron from oxalic acid

Abstract: The electrosynthesis of polyaniline at iron from an oxalic acid solution and at platinum from a sulphuric acid solution was compared with a view to determining the extent of film degradation during formation of polyaniline at iron. It was found that polyaniline grown from oxalic acid is less susceptible to degradation, due to the shielding effect of the oxalate counter anions. The benzoquinone/hydroquinone redox couple was detected for polyaniline films formed on platinum and cycled to 1.3 V/SCE, however, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…It was observed that electrosynthesis of PANI film was affected from electropolymerization conditions such as electrolyte solution and potential range. On the other hand, the upper potential limit during the film growth was slightly higher than the degradation potential value for PANI, which is given as þ0.75 V [14,17] . However, it must be noted that the narrow potential range was unsuitable for homogenous and smooth PANI film in sodium oxalate medium.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…It was observed that electrosynthesis of PANI film was affected from electropolymerization conditions such as electrolyte solution and potential range. On the other hand, the upper potential limit during the film growth was slightly higher than the degradation potential value for PANI, which is given as þ0.75 V [14,17] . However, it must be noted that the narrow potential range was unsuitable for homogenous and smooth PANI film in sodium oxalate medium.…”
Section: Resultsmentioning
confidence: 86%
“…Especially, there are the most studies that report anticorrosive applications of electrochemically synthesized conducting polymers [6][7][8][9][10][11][12][13][14] . However, the protection efficiency of primer coatings are quite limited for MS in artificial seawater.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Utilizing the generative rate of the product QI and the absorption spectra of BQ in the degradation solution to measure the extent of the films degradation in H 2 SO 4 , the results were shown in Figures 6 and 7. In Figure 6, the peak current of the third anodic wave (peak c) had been plotted vs. cycle number at a constant scan rate.…”
Section: Resultsmentioning
confidence: 99%
“…[34,35] The TG and DTG curves show that the composite mainly undergoes four stages of degradation: a) loss of adsorbent water; b) removal of small molecules, such as bound water, NH 4þ and oligmers; c) degradation of polymeric chains; d) decomposition of polyaniline backbone and benzene ring-opening accompanying by other degradation processes ( Figure 5). [26] The TGA results for pure copper and the particulate composite under air atmosphere ( Figure 5) show that: First compositeoxidation is more stable than pure copper; second there are both weigh loss and weight gain stages in these curves and weigh gain proceeded just after some weigh loss. These The final weight ratio of pure copper and compositeoxidation are 125.0% and 112.5%.…”
Section: Thermal Analysis Of the Composites And Discussionmentioning
confidence: 98%